"A Friendly Place to Grow as an Educator": A Qualitative Study of Community and Relationships Among Medical Student Coaches. (February 2020) - Sheu, Leslie; Hauer, Karen E.; Schreiner, Katherine; van Schaik, Sandrijn M.; Chang, Anna; O'Brien, Bridget C.
Abstract : Purpose: The rise of coaching programs in medical education sparks questions about ways to support physician coaches in learning new educational practices specific to coaching. How coaches learn from one another is of particular interest considering the potential value of social learning. Using communities of practice as a conceptual framework, the authors examine the sense of community and relationships among coaches in a new medical student coaching program, the value of this community, and the facilitators and barriers influencing community development. Method: In this qualitative study, investigators conducted 34 interviews with physician coaches at 1 institution over 2 years (2017–2018) and observed 36 coach meetings. Investigators analyzed interview transcripts using thematic analysis and used observation field notes for context and refinement of themes. Results: Coaches described a sense of community based on regular interactions; shared commitment to medical education; and new roles with similar experiences, joys, and challenges. They valued the sense of camaraderie and support, learning from one another, and opportunities for professional growth that strengthened their identities as educators and enhanced job satisfaction. Facilitators of community included regular meetings, leadership and administrative support, and informal opportunities to interact outside of meetings. Barriers included time constraints and geographic challenges for coaches at off-site locations. Conclusions: The sense of community among coaches was a valued and beneficial part of their coaching experience. Coaches' interactions and relationships promoted skill acquisition, knowledge transfer, professional development, and career satisfaction. Thus, incorporating support for social learning in coaching programs promotes coach faculty development. Abstract : Supplemental Digital Content is available in the text.